KUALITAS BAKTERIOLOGI AIR MINUM ISI ULANG DITINJAU DARI METODE DISINFEKSI YANG DIGUNAKAN DI KABUPATEN NGAWI - Prayitno, Suhadi (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
Cases, concerns and complaints in public about refill drinking water, low businessmen DAMIU are checked routinely product processed as well as the mandate of the Consumer Protection Act, Kepmerindag RI and Permenkes RI on monitoring refill drinking water background for the author to conduct research. Purpose to describe the bacteriological quality of refill drinking water in terms of disinfection method used in District Ngawi. This method is descriptive study and cluster sampling to 49 samples DAMIU in District Ngawi with the results of the method used, namely ultraviolet disinfection, ozonation and reverse osmosis. The results bacteriological quality (total coliforms) of any disinfection method shows a different picture, which shows the method of disinfection reverse osmosis bacteriological quality with the percentage of 50.00%, followed by ozonation method of 46.15% and the latter by the ultraviolet method percentage value 44.12 %. The ability of any reduction in total coliform disinfection method shows a different picture, in which the reverse osmosis method of disinfection showed total coliform reduction percentage of 94.08%, followed by ozonation method of 91.46% and the latter by the ultraviolet method percentage value 86.09%. The conclusion willingness, support and cooperation of all stakeholders is needed to improve the supervision, guidance and inspection of the quality of refill drinking water in Ngawi. Key word : water, disinfection, coliform